2017
DOI: 10.1002/jcp.25730
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Notch1 Signaling in Regulating Satellite Cell Fates Choices and Postnatal Skeletal Myogenesis

Abstract: Adult skeletal muscle stem cells, also called satellite cells, are indispensable for the growth, maintenance, and regeneration of the postnatal skeletal muscle. Satellite cells, predominantly quiescent in mature resting muscles, are activated after skeletal muscle injury or degeneration. Notch1 signaling is an evolutionarily conserved pathway that plays crucial roles in satellite cells homeostasis and postnatal skeletal myogenesis and regeneration. Activation of Notch1 signaling promotes the muscle satellite c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…In 2016, Shan et al reviewed that activation of Notch1 signaling promotes the muscle satellite cells’ quiescence and proliferation [ 45 ]. To date, several studies have confirmed several specific genes and miRNAs regulating the proliferation of satellite cells through the Notch signaling pathway [ 39 , 40 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Shan et al reviewed that activation of Notch1 signaling promotes the muscle satellite cells’ quiescence and proliferation [ 45 ]. To date, several studies have confirmed several specific genes and miRNAs regulating the proliferation of satellite cells through the Notch signaling pathway [ 39 , 40 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…After binding with its ligand, Notch is activated by γ‐secretase‐dependent proteolysis within the transmembrane domain to release the Notch intracellular domain (NICD). Then, the NICD translocates into the nucleus and associates with the constitutive DNA‐binding protein CSL to activate transcription of downstream targets, such as Hes1 and Hes5 . However, the evidence regarding the association between Nrf2 and Notch signaling is inconsistent .…”
Section: Introductionmentioning
confidence: 99%
“…Then, the NICD translocates into the nucleus and associates with the constitutive DNA-binding protein CSL to activate transcription of downstream targets, such as Hes1 and Hes5. [18][19][20][21] However, the evidence regarding the association between Nrf2 and Notch signaling is inconsistent. 22,23 Furthermore, few studies have investigated this association in the male reproductive system.…”
mentioning
confidence: 99%
“…[13] On the other hand, roles of Notch1 Signaling in regulating satellite cell fates choices and postnatal skeletal myogenesis had been confirmed, and human skeletal muscle fibroblasts can stimulate in vitro myogenesis and in vivo muscle regeneration. 26 Wnt/β-catenin signalling also paly a important role to promote stem cells to repair injured tissue. In a previous in vitro study, the results showed that the canonical Wnt/β-catenin pathway promoted the differentiation of Mesenchymal stem cells (MSCs) into type II alveolar epithelial cells.…”
Section: Pax7 β-Catenin Expressionmentioning
confidence: 99%